Malay Maritime World in Southeast Asia - Bondan Kanumoyoso (Diponegoro University, 2018)
The development of maritime activities in Southeast Asia in the “Age of Commerce” was strongly support by the Malay people. although Westerners have begun to dominate maritime activities in the region since the 17th century, but in the same period Malays and their trading networks continue to perform their irreplaceable function of connecting the various maritime communities that scattered throughout Southeast Asia. The extent of the Malay trade network was one of the factors that shape the maritime character of Southeast Asia. However, Malay trading activities was not only encouraged economic development in this region, but also form an identity that can be called as Malay maritime world of Southeast Asia. This article examines the maritime characteristic of Malay world and how global trade actually strengthens the role of Malay in trade and other maritime activities.